Pengaruh Penggunaan Artificial Intelligence (AI) terhadap Keterampilan Berbicara Kritis dan Menulis Kritis - Hasnatan Hasnatan; Nensilianti Nensilianti; Sultan Sultan (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
This study aims to determine the effect of using Artificial Intelligence (AI), specifically ChatGPT, on the critical speaking and critical writing skills of Grade X students at UPT SMA Negeri 3 Bone. The research employed a quantitative method with a true experimental design using a pretest-posttest control group model. Data were collected through tests administered before and after the treatment, and analyzed using descriptive and inferential statistics. The results showed a significant improvement in students’ critical speaking skills (from 71.51 to 80.03) and critical writing skills (from 73.96 to 91.33) after the use of AI. T-test results indicated statistically significant differences (Sig. < 0.05) in both paired and independent samples. These findings confirm that AI use is effective in enhancing students’ critical speaking and writing skills.